LIBERAL ISLAM IN THE CONTEMPORARY WORLD: NEW LANDMARKS OF TRUMP’S ADMINISTRATION - BAFOEV, Feruz (CENTRAL ASIA AND THE CAUCASUS, 2019)
The article discusses the opposition between the antagonists and pragmatics in the highest political and military circles of the United States, who disagree on the ideology and practice of contemporary Islam. It demonstrates that Muslim communities, new diasporas, pro-Islamic public organizations, human rights organizations, influential media, and think-tanks in the United States are gradually gaining influence. The article highlights the apparent bias of Donald Trump’s administration towards relevant trade and financial gains. The developing American model of liberal Islam is described as fairly specific, systemic, and consistent. The study reveals what the U.S. administration thinks about post-conflict reconstruction in Afghanistan, Syria, Iraq, Libya, and other countries. It also points out the new aspects of its cooperation with Central Asian and Caucasian countries, as well as the response to issues related to the realization of religious freedom rights and opposition to religious extremism.